Inovasi Manajemen Controlling dalam Pengelolaan Usaha Berbasis Syariah di Era Digital - Camelia, Rizqiatul Camelia; Permana, Dikki; Rohmah, Fathur; Muaffa, Muhammad Alif; Addina, Nadia Izza; Zubaidah, Siti (UMSurabaya Publishing, 2025)
This study aims to analyze the practice of controlling management in a Madura grocery store (Warung Madura) located in Telang Village from an Islamic economic perspective. The research employed a qualitative method with a single case study design, collecting data through in-depth interviews, observation, and documentation. The findings reveal that although controlling practices remain simple, such as manual financial recording, stock management, and capital reinvestment, the store owner consistently applies Islamic principles, including fair pricing, reasonable profit margins, and trustworthiness in capital management. Digital innovation is evident through the use of QRIS, although the application of financial and inventory management systems is still limited. The limitation of this study lies in its focus on a single store, which makes the results contextual and not generalizable. Nevertheless, this research provides practical implications for the development of Sharia-based micro, small, and medium enterprises (MSMEs) and theoretical contributions by reinforcing the relevance of Islamic principles in controlling practices for microbusinesses. Keywords: controlling management, Warung Madura, Islamic economics, digitalization, case study Penelitian ini bertujuan untuk menganalisis praktik manajemen controlling pada salah satu Warung Madura di Desa Telang dalam perspektif ekonomi syariah. Metode penelitian menggunakan pendekatan kualitatif dengan desain studi kasus tunggal, di mana data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa meskipun praktik controlling masih sederhana, seperti pencatatan manual keuangan, pengelolaan stok, dan reinvestasi modal, pemilik warung konsisten menerapkan prinsip syariah, seperti keadilan harga, margin keuntungan yang wajar, dan amanah dalam pengelolaan modal. Adopsi inovasi digital terlihat dari penggunaan QRIS, meski pemanfaatan aplikasi manajemen keuangan dan inventori masih terbatas. Keterbatasan penelitian ini adalah hanya meneliti satu warung, sehingga hasilnya bersifat kontekstual dan belum dapat digeneralisasi. Penelitian ini memiliki implikasi praktis bagi pengembangan UMKM berbasis syariah serta memberikan kontribusi teoretis sebagai studi kasus yang menegaskan relevansi prinsip syariah dalam praktik controlling usaha mikro. Kata Kunci: Manajemen controlling, Warung Madura, ekonomi syariah, digitalisasi, studi kasus